DEIXIS AND REFERENCE ANALYSIS IN JAKARTA POST: A CONTENT ANALYSIS RESEARCH - Syafryadin Syafryadin; Eka Apriani; Rita Inderawati; Wawan Tarwana; Haryani Haryani (STKIP Persada Khatulistiwa Sintang, 2021)
Deixis and reference are parts of pragmatics. These issues are needed to be known by the readers. Deixis and reference were existing in written or spoken language and those materials are learnt by students in university level especially in English education department. These things are essential to be known by the readers or audience. Thus, the aims of the study were to analyse the deixis and reference types in Jakarta Post. The research methodology was a qualitative research with content analysis. The instruments were checklist and document. Those were validated by triangulation. There were 90 articles of Jakarta Post to be analysed by using a thematic analysis. The steps were familiarization, coding, generating themes, defining and naming themes and writing up stage. The results showed that all types of dexis were found in Jakarta Post namely person, Spatial, time, discourse and social. In detail, 300 words of person deixis, 140 Spatial deixis, 90 time deixis, 30 social and 15 discouse deixis. The dominant type was person deixis. Another result was reference. The anaphoric and cataphoric reference were found in Jakarta Post, where the dominant one is anaphoric reference. In short, most of authors in Jakarta Post used person deixis and anaphoric reference to give clear information about the written text.